Alteration out of sight: a petrographic and HyLogger study of the McPhillamys gold deposit, east Lachlan Orogen, New South Wales - J. Fitzherbert; K. Hughes; K. Montgomery; P. Downes; C. Folkes; J. Egan; P. Flitcroft; S. Bodorkos; H. Huang (Australian Journal of Earth Sciences, 2026)

Origin and HFSE enrichment potential of a Late Cretaceous basalt to peralkaline rhyolite suite in central Queensland, Australia - D. Purdy; B. Simpson; N. Kositcin; J. Fitzherbert; H. Dalton (Australian Journal of Earth Sciences, 2025)

Basin provenance and its control on mineralisation within the Early Devonian Cobar Basin, western Lachlan Orogen, eastern Australia - B. Yang; R. Offler; J. A. Fitzherbert; C. Folkes; R. Dwyer; C. Clark (Australian Journal of Earth Sciences, 2024)

Early Devonian volcanic facies, central Lachlan Orogen, New South Wales: implications for tectonic and metallogenic models - K. F. Bull; J. A. Fitzherbert (Australian Journal of Earth Sciences, 2022)

Regional metamorphism and the alteration response of selected Silurian to Devonian mineral systems in the Nymagee area, Central Lachlan Orogen, New South Wales: a HyLogger™ case study - P. M. Downes; D. B. Tilley; J. A. Fitzherbert; M. E. Clissold (Australian Journal of Earth Sciences, 2016)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Conservation in Oil‐Palm Landscapes - Ben Phalan; Emily B. Fitzherbert; Sylvain Rafflegeau; Matthew J. Struebig; Aude Verwilghen (Conservation Biology, 2009)